Level of Leadership Competencies Among Junior High School (JHS) Teachers Towards Addressing Academic Challenges of Students: A Basis for Proposed Action Plan - Emmanuela Joy M. Silva; Lourdes Ibe-Nati (Researchparks Publishing, 2026)
The study examined Junior High School teachers’ leadership competencies (instructional and organizational) and the academic challenges of learners, integrating quantitative results with student perspectives to inform an action-oriented response. Overall, teachers demonstrated excellent instructional leadership (Composite Mean = 4.610), suggesting strong alignment of curriculum, instruction, assessment, and feedback practices. Teachers also exhibited excellent organizational leadership (Composite Mean = 4.460), reflecting effective classroom management, collaboration, communication with stakeholders, and culture building. Regarding student academic challenges, teachers reported ineffective study habits as occurring often (Composite Mean = 3.593), indicating persistent concerns in time management, procrastination, distraction, and limited help-seeking. Other challenges—low motivation/engagement, comprehension/performance difficulties, irregular participation/attendance, and limited access to learning resources/support—were generally observed sometimes, implying variability across learners and contexts. Relational analyses further indicated targeted links between leadership and specific difficulties. Instructional leadership showed a significant inverse association with irregular participation/attendance (Spearman ρ = −.34, p = .002), while organizational leadership demonstrated a significant inverse association with limited access to learning resources/support (Spearman ρ = −.23, p = .040). These findings suggest that stronger leadership practices are associated with fewer selected challenges, although effects are modest and likely context-dependent. Qualitative accounts converged with the quantitative patterns: students emphasized clear explanations, patience, varied strategies, checks for understanding, encouragement, and fair discipline, while also noting inconsistency across teachers and uneven resource provision. Consequently, the proposed action plan should prioritize instruction, attendance/participation supports, and coordinated resource mobilization, with monitoring anchored in attendance logs, formative assessment records, and structured learner feedback. Regarding student academic challenges, teachers reported ineffective study habits as occurring often (Composite Mean = 3.593), indicating persistent concerns in time management, procrastination, distraction, and limited help-seeking. Other challenges—low motivation/engagement, comprehension/performance difficulties, irregular participation/attendance, and limited access to learning resources/support—were generally observed sometimes, implying variability across learners and contexts. Relational analyses further indicated targeted links between leadership and specific difficulties. Instructional leadership showed a significant inverse association with irregular participation/attendance (Spearman ρ = −.34, p = .002), while organizational leadership demonstrated a significant inverse association with limited access to learning resources/support (Spearman ρ = −.23, p = .040). These findings suggest that stronger leadership practices are associated with fewer selected challenges, although effects are modest and likely context-dependent. Qualitative accounts converged with the quantitative patterns: students emphasized clear explanations, patience, varied strategies, checks for understanding, encouragement, and fair discipline, while also noting inconsistency across teachers and uneven resource provision. Consequently, the proposed action plan should prioritize instruction, attendance/participation supports, and coordinated resource mobilization, with monitoring anchored in attendance logs, formative assessment records, and structured learner feedback.